2009
DOI: 10.1002/j.1556-6978.2009.tb00083.x
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and Counseling Self‐Efficacy: The Mediating Role of Attention and Empathy

Abstract: This study examined the predictive relationship between mindfulness and counseling self-efficacy and the potential mediating effects of attention and empathy. Master's-level counseling interns and doctoral counseling students (N = 179) were surveyed to determine levels of mindfulness, attention, empathy, and counseling self-efficacy. Pearson product-moment correlation coefficients revealed significant pairwise relationships between the 4 variables of interest. A multiplemediator path analysis supported the hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
207
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(233 citation statements)
references
References 53 publications
22
207
0
4
Order By: Relevance
“…Therefore, strengthening the protective factors associated with resilience will strengthen resilience. Thompson, Arnkoff, and Glass (2011) have proposed that mindfulness is associated with resilience, and Greason & Cashwell (2009) research found evidence of an association between mindfulness and self-efficacy. These findings suggest that mindfulness and self-efficacy show potential to be protective factors to strengthening resilience (Hamill, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, strengthening the protective factors associated with resilience will strengthen resilience. Thompson, Arnkoff, and Glass (2011) have proposed that mindfulness is associated with resilience, and Greason & Cashwell (2009) research found evidence of an association between mindfulness and self-efficacy. These findings suggest that mindfulness and self-efficacy show potential to be protective factors to strengthening resilience (Hamill, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Yoga, meditation, and qigong have also been used in counselor education resulting in beneficial personal and professional outcomes (Christopher, Christopher & Dunnagan, 2006). Other mindfulness practices have been recommended for increasing student self-efficacy in counseling practice (Greason & Cashwell, 2011). It is useful to consider the types of activities that could be incorporated into the academic coursework, encouraged by faculty advisors, or led by peers through student organizations such as Chi Sigma Iota.…”
Section: Discussionmentioning
confidence: 99%
“…Pamukçu, 2011 göre danışman öz-yeterlik inancı ne yapacağını bilme il eylemi gerçekleştirme arasında aracı rolündedir ve aynı zamanda etkili danışmanın birincil belirleyicisidir. Bu çerçevede alan yazında psikolojik danışman adaylarının öz-yeterlik algıları (Aksoy ve Diken, 2009;Greason ve Cashwell, 2009;Pamukçu, 2011;Meyer, 2012;Öztürk, 2014) ile ilgili çalışmalar olmakla beraber, psikolojik danışmanların öz-yeterlik algıları (Can, 2010;Cheng ve diğ., 2011;Gündüz, 2012;Haron, Jaafar ve Baba, 2010;Larson ve Daniels, 1998;Owens, Bodenhorn ve Bryant, 2010;Sali Bilgiç, 2011;Yüksel ve diğ., 2012) ile ilgili çalışmalar da bulunmaktadır.…”
Section: öğRetmen öZ-yeterliğiunclassified
“…Yüksel ve diğerlerine (2012) göre de rehber öğretmen adaylarının psikolojik danışma ve rehberliğe ilişkin alınan eğitimlerin miktarı arttıkça öz-yeterlik düzeylerinin de arttığı yönündedir. Bunun yanında psikolojik danışmanların yaşam doyumları (Pamukçu, 2011) ve işleri ile ilgili farkındalıkları (Greason ve Cashwell, 2009) arttıkça öz-yeterlik algıları da artacaktır. Yine Haron, Jaafar ve Baba (2010) okul ikliminin psikolojik danışmanlarının öz-yeterliğini etkilediğini bulmuşlardır.…”
Section: Tartişma Sonuç Ve öNeri̇lerunclassified